AB1011 Anti-TNF using ankylosing spondylitis patients may have less severe osteoporosis. (23rd January 2014) - Dolasik, I.; Cosan, F.; Yilmazer, B.; Cefle, A.
Abstract : Background: Ankylosing spondylitis (AS) is a systemic chronic inflammatory disease characterized with enthesitis. The risk of osteoporosis is increased in AS. Low bone mineral dencity is found associated with systemic inflammation. Objectives: We aimed in this study to investigate the risk of osteoporosis in AS patients using anti- TNF treatment. Methods: The study group consisted of 49 AS patients who are using anti-TNF therapy more than 6 months, and the control group 47 AS patients without anti-TNF therapy. Two groups had similar age distribution at the time of bone mineral dansitometry. No patient had received steroid therapy previously. Results: The total femoral T score was higher in AS group with anti-TNF treatment in comparison to the control group (p=0, 033; mean T scores: -0, 97 and -1, 53, respectively). The T scores of total lomber vertebra was higher in AS group with anti-TNF therapy than the control group (p=0, 046, mean T scores: 0, 0 and -0, 81, respectively). The mean femoral BMD value in the anti-TNF therapy group was 0, 92 g/cm 2 (in comparing to 0, 78 g/cm 2 ) and was signifacantly higher (p=0, 002). Moreover the lomber vertebra BMD value was significantly higher in the anti-TNF group (p=0, 001, mean BMD values: 1, 20 g/cm 2 and 1, 03 g/cm 2, respectively). Conclusions: Our data revealed that AS patients receiving anti-TNF therapy have more less osteoporosis. The anti-TNF therapy may reduce the risk of osteoporosis in AS patients. Disclosure of Interest: None Declared